The quantified method for blood clot detection in the extraction socket [version 1; peer review: 1 approved, 2 approved with reservations] - Piyachat Patcharanuchat; Sajee Sattayut; Suwat Tanya (F1000Research)
Background Currently, there is no objective and quantified measurement for detecting blood clots during extraction socket hemostasis. It has relied solely on clinical observation, even when conducting clinical research by using extraction sockets as samples. This study aimed to assess the in vitro reliability and clinical-relevant validity of a new objective measurement providing quantified data called blood clot detection (BCD) using a standard capillary tube. Methods The in vitro part of the study was conducted using surplus blood samples from ten healthy participants. Two identical sets of blood samples in simulation reservoirs mimicking bleeding sockets were prepared for reliability tests. Then, the capillary tubes were concurrently placed in the reservoirs. The blood-filled distances were measured. The part of clinical-relevant validity study was conducted in sixteen extraction sockets from each healthy participant. Clinical observation and BCD measurement were evaluated by two calibrated assessors. The total duration of the assessment was a 30-minute. Results The distances of the blood-filled capillary tube were decreased by time. Test and retest reliability analysis of the BCD measurement showed an excellent intraclass correlation coefficient of 0.980 (0.968 to 0.988). The medians of blood-filled distance categorized by clinical observation into active bleeding, sluggish oozing, and clot formation were 13.0 mm (Q1 = 11.7, Q3 = 13.8), 5.6 mm (Q1 = 4.3, Q3 = 7.0), and 0.9 mm (Q1 = 0.5, Q3 = 1.3), respectively. The blood-filled distance of the clot formation group was significantly less than the active bleeding and sluggish oozing (p<0.001). Therefore, the BCD measurement also significantly indicated the completion of extraction socket hemostasis Conclusions A distance of blood-filled in capillary tube of 0.9 mm from the BCD measurement significantly ensured complete clot formation. The BCD measurement proved to be a quantified tool for objectively measuring hemostasis of bleeding socket.